Present Situation of Treatment and Utilization of Rural Sewage Constructed Wetland in Loess Plateau - Wei, Yulu (Scientific Journal of Technology, 2025)
With the improvement of living standards, the output of rural domestic sewage is also increasing. How to treat sewage and effectively use sewage has become the main technical bottleneck restricting the social and economic development of the Loess Plateau. The construction cost of constructed wetland is low, the construction form is flexible, and the landscape greening of courtyards and villages can be organically combined with the sewage treatment, which is in line with the guiding direction of local sewage consumption in rural areas. The existing problems of rural sewage treatment are analyzed, and the development status and prospect of constructed wetland are discussed.